2016
DOI: 10.3109/10428194.2016.1142086
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic characterization of imatinib-resistant BCR-ABL T315I chronic myeloid leukemia cells indicates down-regulation of glycolytic pathway and low ROS production

Abstract: Long-term imatinib treatment induces drug-resistant chronic myeloid leukemia (CML) cells harboring T315I gate keeper mutation of breakpoint cluster region (BCR)-ABL oncogenic kinase. However, although cell proliferation is coupled with cellular energy status in CML carcinogenesis, the metabolic characteristics of T315I-mutant CML cells have never been investigated. Here, we analyzed cell proliferation activities and metabolic phenotypes, including cell proliferation, oxygen consumption, lactate production, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…During OXPHOS, reactive oxygen species (ROS) are generated by mitochondria [17]. We found decreased intracellular ROS levels in both resistant cell lines as compared to their sensitive parental cells ( Figure S5), which is concordant with a low ROS production in imatinib-resistant chronic myeloid leukemia cell lines [18].…”
Section: Heterogeneity Of Energy Metabolism Among Imatinib-resistant supporting
confidence: 66%
“…During OXPHOS, reactive oxygen species (ROS) are generated by mitochondria [17]. We found decreased intracellular ROS levels in both resistant cell lines as compared to their sensitive parental cells ( Figure S5), which is concordant with a low ROS production in imatinib-resistant chronic myeloid leukemia cell lines [18].…”
Section: Heterogeneity Of Energy Metabolism Among Imatinib-resistant supporting
confidence: 66%
“…Previous research has shown that GPx1 is an effective antioxidant enzyme that cannot be replaced by any other selenoprotein to protect against generalized oxidative stress [74][75][76]. When cancerous cells are generated, the expression of GPx1 is abnormal, causing intracellular ROS dysfunction [77,78]. Due to its antioxidant properties, GPx1 is thought to be highly effective in preventing the ROS-mediated initiation of cancer.…”
Section: Gpx1mentioning
confidence: 99%
“…Selected recent research indicates that cells resistant to IM demonstrate lower levels of expression of ROS scavengers such as GPx and catalase [40]. Interestingly, we observed that after exposure to IM the GPx and catalase activity increased in IM-resistant CML cells in comparison to IM-susceptible cells.…”
Section: Discussionmentioning
confidence: 46%
“…On the other hand, it has been recently demonstrated that CML cells resistant to IM through T315I mutation exhibit a lower level of ROS production when compared to CML cells susceptible to IM action. However, those results were gathered using a different cell lines than the ones used by us, which might serve as an explanation for the observed differences [40].…”
Section: Discussionmentioning
confidence: 87%